High-pass filter settings and the role and mechanism of discrete ventricular electrograms in left bundle branch pacing - Shen, Jiabo; Jiang, Longfu; Wu, Hao; Li, Hengdong; Zhang, Lu; Zhong, Jinyan; Zhuo, Shanshan; Pan, Lifang (Frontiers in Cardiovascular Medicine, 2023)
Abstract Objective: The characteristics of discrete intracardiac electrogram (EGM) in selective left bundle branch (SLBB) pacing (SLBBP) have not been described in detail previously. This study aimed to examine the effect of different high-pass filter (HPF) settings on discrete local ventricular components in an intracardiac EGM and to analyze its possible mechanisms. Methods: This study included 144 patients with indications of permanent cardiac pacing. EGMs were collected at four different HPF settings (30, 60, 100, and 200 Hz) with a low-pass filter at 500 Hz, and their possible mechanisms were analyzed. Results: LBBP was successfully achieved in 91.0% (131/144) of patients. SLBBP was achieved in 123 patients. The occurrence rates of discrete local ventricular EGM were 16.7%, 33.3%, 72.9%, and 85.4% for HPF settings of 30 Hz, 60 Hz, 100 Hz, and 200 Hz, respectively. The analysis of discrete EGM detection showed significant differences between the different HPF settings. By using the discrete local ventricular component and isoelectric interval as the SLBB capture golden standard, the results of EGMs revealed that the 30 Hz HPF has a sensitivity of 19% and specificity of 100%. The 60 Hz HPF had a sensitivity of 39% and a specificity of 100%. The 100 Hz HPF had a sensitivity of 85% and a specificity of 100%. The 200 Hz HPF had a sensitivity of 100% and specificity of 100%. Conclusions: An optimal HPF setting of 200 Hz is recommended for discrete local ventricular EGM detection. A discrete local ventricular EGM should exhibit an isoelectric interval. A steep deflection and high-frequency ventricular EGM morphology nearly identify an intrinsic EGM morphology.